Assessment of maternal and fetal outcome in trial of labor after cesarean - Beer, Sunita Kumari; Chaudhary, Jaya; Tiwari, Kalpana; Choudhary, Sonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Nowadays, cesarean sections are increasing consistently. Repeat cesarean sections are performed for a large percentage and associated with a higher rate of surgical complications and Long-term morbidities. The trial of labor after cesarean offers an alternative choice. This study carried out to assess the maternal and fetal outcome and to evaluate various parameters as a predictor of success of TOLAC. Methods: This prospective observational study conducted on 150 pregnant women with one previous LSCS who delivered at Mahatma Gandhi hospital, from January 2017 to July 2018. Patient having a singleton pregnancy, cephalic presentation, adequate pelvis size with spontaneous onset of labor were included. Cases were monitored carefully during the labor. Emergency LSCS was done if any indication appeared. Results: 78% of cases delivered safely by the vaginal birth and 22% of cases had an emergency repeat cesarean section (EmRCS). Favorable Bishop Score, active stage of labor and prior vaginal delivery were associated with higher success rate. One (0.66%) case of uterine scar rupture and 2 (1.33%) cases of scar dehiscence noted. No maternal mortality observed. Perinatal mortality occurred in 2 cases (1.33%). Conclusions: Present study shows that appropriate clinical settings and the properly selected group of patients can make the TOLAC safe and effective.